Impact of Sea Ice Melting on Summer Air-Sea CO2 Exchange in the East Siberian Sea - Mo, Ahra; Yang, Eun Jin; Kang, Sung-Ho; Kim, Dongseon; Lee, Kitack; Ko, Young Ho; Kim, Kitae; Kim, Tae-Wook (Frontiers in Marine Science, 2022)
The role of sea ice melting on the air-sea CO2 flux was investigated at two ice camps in the East Siberian Sea of the Arctic Ocean. On average, sea ice samples from the two ice camps had a total alkalinity (TA) of ∼108 and ∼31 μmol kg–1 and a corresponding salinity of 1.39 and 0.36, respectively. A portion (18–23% as an average) of these sea ice TA values was estimated to exist in the sea ice with zero salinity, which indicates the excess TA was likely attributed to chemical (CaCO3 formation and dissolution) and biological processes in the sea ice. The dilution by sea ice melting could increase the oceanic CO2 uptake to 11–12 mmol m–2 d–1 over the next 21 days if the mixed layer depth and sea ice thickness were assumed to be 18.5 and 1.5 m, respectively. This role can be further enhanced by adding TA (including excess TA) from sea ice melting, but a simultaneous release of dissolved inorganic carbon (DIC) counteracts the effect of TA supply. In our study region, the additional impact of sea ice melting with close to unity TA:DIC ratio on air-sea CO2 exchange was not significant.